Mineralogy and distribution of critical elements in the Sn–W–Pb–Ag–Zn huanuni deposit, bolivia - Cacho, A.; Melgarejo i Draper, J.C.; Camprubí, A.; Torró, L.; Castillo-Oliver, M.; Torres, B.; Artiaga, D.; Tauler, E.; Martínez, Á.; Campeny, M.; Alfonso, P.; Arce-Burgoa, O.R. (MDPI, 2019)
The polymetallic Huanuni deposit, a world-class tin deposit, is part of the Bolivian tin belt. As a likely case for a “mesothermal” or transitional deposit between epithermal and porphyry Sn types (or shallow porphyry Sn), it represents a case that contributes significantly to the systematic study of the distribution of critical elements within the “family” of Bolivian tin deposits. In addition to Sn, Zn and Ag, further economic interest in the area resides in its potential in critical elements such as In, Ga and Ge. This paper provides the first systematic characterisation of the complex mineralogy and mineral chemistry of the Huanuni deposit with the twofold aim of identifying the mineral carriers of critical elements and endeavouring plausible metallogenic processes for the formation of this deposit, by means of a multi-methodological approach. With In concentrations consistently over 2000 ppm, the highest potential for relevant concentrations in this metal resides in widespread tin minerals (cassiterite and stannite) and sphalerite. Hypogene alteration assemblages are hardly developed due to the metasedimentary nature of host rocks, but the occurrence of potassium feldspar, schorl, pyrophyllite and dickite as vein material stand for potassic to phyllic or advanced argillic alteration assemblages and relatively high-temperature (and low pH) mineralising fluids. District-scale mineralogical zonation suggests a thermal zonation with decreasing temperatures from the central to the peripheral areas. A district-scale zonation has been also determined for δ³⁴SVCDT values, which range −7.2‰ to 0.2‰ (mostly −7‰ to −5‰) in the central area and −4.2‰ to 1.0‰ (mainly constrained between −2‰ and 1‰) in peripheral areas. Such values stand for magmatic and metasedimentary sources for sulfur, and their spatial zoning may be related to differential reactivity between mineralising fluids and host rocks, outwardly decreasing from the central to the peripheral areas.
Keywords: Polymetallic deposit; Critical elements; Tin belt; https://purl.org/pe-repo/ocde/ford#1.05.02